An elastoplastic model for cohesionless soils under a wide range of confining pressures - Linlong Mu; Shunwei Wang; Xiaoxiang Chen; Yimin Lu (European Journal of Environmental and Civil Engineering, 2026)

Inclusion of cyclic loading characteristics in a load–transfer analysis for jacket foundation piles in clay - Guangming Yu; Kewen Zhu; Hang Feng; Junlin Zhu; Linlong Mu (Marine Georesources & Geotechnology, 2026)

Experimental characterization and design implications on vertical dynamic response of suction bucket foundation in saturated sand - Linlong Mu; Tao Zhou; Yimin Lu (Ocean Engineering, 2026)

Ultimate soil resistance analysis of horizontally loaded piles in c-φ soils: a modified p-y curve formulation - Linlong Mu; Shunwei Wang; Xiaoxiang Chen; Jiawei Zhang; Guangming Yu (Ocean Engineering, 2026)

Dynamic response of high-piled wharf under wave excitation considering local scour - Linlong Mu; Tao Zhou; Yimin Lu; Maosong Huang; Shen Zhou; Meihe Chen (Soil Dynamics and Earthquake Engineering, 2025)

Rate-dependent uplift behavior and soil failure mechanisms of suction anchors in loose sand: a transparent soil PIV study - Tao Zhou; Linlong Mu; Yimin Lu; Meihe Chen; Maosong Huang; Yuxuan Li (Ocean Engineering, 2025)

Global Fixed-Time Target Enclosing Tracking Control for an Unmanned Surface Vehicle Under Unknown Velocity States and Actuator Saturation - Xinjie Han; Guanglu Ma; Yunsheng Fan; Dongdong Mu; Feng Sun; Linlong Shi; Hongbiao Li (Journal of Marine Science and Engineering, 2025)
This paper presents a global fixed-time control framework to address the target circumnavigation tracking problem of underactuated unmanned surface vehicles (USV) under unknown velocity states, lumped uncertainties, and actuator saturation. At the core of this approach is a novel fixed-time target-enclosing line-of-sight (FTTELOS) guidance law, designed to generate the desired heading angle and surge velocity. To estimate unknown velocities, external disturbances, and unmeasured system states, a set of fixed-time observers is constructed, consisting of a velocity observer, a disturbance observer, and a high-dimensional extended state observer (HFTESO). Moreover, to enhance robustness and effectively tackle actuator saturation, the control scheme incorporates a fixed-time sliding mode controller, a dynamic auxiliary system, and a fixed-threshold event-triggered mechanism. Simulation results using SimuNPS demonstrate that the proposed method enables rapid and smooth target circumnavigation, with all system errors converging to an arbitrarily small neighborhood of the origin within a fixed time. Theoretical analysis and simulation studies confirm the effectiveness and robustness of both the FTTELOS guidance law and the integrated control strategy. Quantitatively, compared with the traditional target-enclosing line-of-sight (TELOS) method, the proposed FTTELOS reduces the convergence time of the distance error δe from 13.64 s to 10.22 s and the angular error ϕe from 10.46 s to 7.52 s, demonstrating a significant improvement in convergence speed and overall control performance.

Microscopic insights into local scour around a vertical circular pile under steady current: Coupled LES-CGDEM simulations - Peiyun Zhang; Linlong Mu; Maosong Huang; Xiaoqiang Gu (Computers and Geotechnics, 2025)

Modeling the reachable set of ships in the presence of realistic wave disturbances - Dongdong Mu; Xiaomeng He; Mingyang Yin; Hongbiao Li; Linlong Shi; Yunsheng Fan; Xiaojie Sun (Ocean Engineering, 2025)

Microscopic insights into suction bucket installation in sand: Coupled coarse-grained CFD-DEM simulations - Peiyun Zhang; Linlong Mu; Yimin Lu; Maosong Huang; Jianguo Sun (Computers and Geotechnics, 2024)

Three-dimensional finite element analysis for uplifting independent helix plate anchor in uniform clay - Yunhan Huang; Linlong Mu; Peipei Wang (Ocean Engineering, 2023)

A coupled CFD-DEM investigation into hydro-mechanical behaviour of gap-graded soil experiencing seepage erosion considering cyclic hydraulic loading - Peiyun Zhang; Linlong Mu; Maosong Huang (Journal of Hydrology, 2023)

Nonlinear investigation of laterally loaded piles in layered sand with a modified conical strain wedge model - Xun Zhang; Zhiping Hu; Linlong Mu; Wei Tian; Yaguo Zhang; Pei Huang (Ocean Engineering, 2023)

Predicting longitudinal tunnel deformation due to deep excavation-induced ground movement - Linlong Mu; Peiyun Zhang; Zhenhao Shi; Mengxi Zhu; Zhiwang Gu (Tunnelling and Underground Space Technology, 2023)

Coupled CFD–DEM Investigation of Erosion Accompanied by Clogging Mechanism under Different Hydraulic Gradients - Linlong Mu; Peiyun Zhang; Zhenhao Shi; Maosong Huang (Computers and Geotechnics, 2023)

A framework of analytical methods for horizontal behaviours of monopiles under V-H-M loads in sand - Linlong Mu; Wei Chen; Yiming Zhang; Xiaoxiang Chen; Wan Li (Marine Georesources & Geotechnology, 2022)

Influence of vertical loads on lateral behaviour of monopiles in sand - Linlong Mu; Xingyu Kang; Kai Feng; Maosong Huang; Jie Cao (European Journal of Environmental and Civil Engineering, 2018)